2014
DOI: 10.1038/ncomms6671
|View full text |Cite
|
Sign up to set email alerts
|

miR-205 acts as a tumour radiosensitizer by targeting ZEB1 and Ubc13

Abstract: Tumor cells associated with therapy resistance (radioresistance and drug resistance) are likely to give rise to local recurrence and distant metastatic relapse. Recent studies revealed microRNA (miRNA)-mediated regulation of metastasis and epithelial-mesenchymal transition; however, whether specific miRNAs regulate tumor radioresistance and can be exploited as radiosensitizing agents remains unclear. Here we find that miR-205 promotes radiosensitivity and is downregulated in radioresistant subpopulations of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 64 publications
9
136
0
Order By: Relevance
“…Recent studies have shown that in mouse models, delivery of miR-205 through nanoliposomes can sensitize breast tumors to radiation, 88 and induction of miR-205 expression by an antioxidant negatively modulates epithelial-mesenchymal transition and inhibits triple-negative breast cancer metastasis. 89 Thus, miR-205 may be a potential therapeutic target for advanced breast cancer including inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that in mouse models, delivery of miR-205 through nanoliposomes can sensitize breast tumors to radiation, 88 and induction of miR-205 expression by an antioxidant negatively modulates epithelial-mesenchymal transition and inhibits triple-negative breast cancer metastasis. 89 Thus, miR-205 may be a potential therapeutic target for advanced breast cancer including inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has revealed that miRNA expression profiles are significantly modified in cancer cells undergoing IR. 7,8 Moreover, many studies have shown radioresistance by altering miRNA levels in various malignances, such as laryngeal 12 prostate, 13 nasopharyngeal, 14 and breast 10,11 cancer in vivo and in vitro. To better understand the mechanisms underlying radioresistance in NSCLC, in this study, we investigated the miRNome of a radioresistant cell model for NSCLC, and we identified known and novel miRNAs implicated in radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Thus, miRNA-targeting therapy has been proposed as a novel approach to radioresistant tumor management. Many examples of miRNAs involved in radioresistance have been reported in breast cancer, 10,11 laryngeal carcinoma, 12 prostate cancer, 13 nasopharyngeal cell carcinoma, 14,15 and liver cancer, 16 among other cancers. In lung cancer cells, miRNAs have been described as potential regulators of radiation response.…”
Section: Introductionmentioning
confidence: 99%
“…To improve this situation, it is importance to enhance the radiation sensitivity of esophageal cancers. Recent studies have demonstrated that the process of radioresistance involves multiple molecular mechanisms (Halimi et al, 2012;Qian et al, 2014;Zhang et al, 2014a), and numerous studies suggest that miRNAs played an important role in response to ionizing radiation (Cellini et al, 2014). Previous studies have suggested that miRNAs can act as tumor suppressors by targeting crucial genes (Liu et al, 2013a,b;Yongchun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%